Simultaneous analysis of allopurinol and oxypurinol using a validated liquid chromatography-tandem mass spectrometry method in human plasma - Dhiraj M. Rathod; Keyur R. Patel; Hiren N. Mistri; Arvind G. Jangid; Pranav S. Shrivastav; Mallika Sanyal (Elsevier, 2017)
The present study describes a simple, reliable and reproducible liquid chromatography-tandem mass spectrometry method (LC-MS/MS) for the simultaneous determination of allopurinol and its active metabolite, oxypurinol in human plasma for a pharmacokinetic/bioequivalence study. After protein precipitation (PPT) of 100 µL plasma sample with 1.0% formic acid in acetonitrile, the recovery of the analytes and allopurinol-d2 as an internal standard ranged from 85.36% to 91.20%. The analytes were separated on Hypersil Gold (150 mm×4.6 mm, 5 µm) column using 0.1% formic acid-acetonitrile (98:2, v/v) as the mobile phase. Quantification was done using electrospray ionization in the positive mode. The calibration concentration range was established from 60.0 to 6000 ng/mL for allopurinol and 80.0-8000 ng/mL for oxypurinol. Matrix effect in human plasma, expressed as IS-normalized matrix factors ranged from 1.003 to 1.030 for both the analytes. The developed method was found suitable for a clinical study with 300 mg allopurinol tablet formulation in healthy subjects.